"Nutcracker Fracture" in a Ballet Dancer Performing in the Nutcracker. Issue 3 (September 2015) - Carsen, Sasha; Quinn, Bridget J.; Beck, Elizabeth; Southwick, Heather; Micheli, Lyle J.
A 26-year-old female professional dancer sustained an acute injury to her mid-foot during a performance of The Nutcracker. An intra-articular, comminuted, minimally displaced fracture of the cuboid was found. The patient was treated non-operatively with cast and boot immobilization, modified weightbearing, and progressive rehabilitation. She was able to return to professional dance at 6 months post-injury and continues to dance professionally over 1 year out from injury without issue. The unique demands of classical ballet, especially dancing en pointe, increase the risk for mid-foot fractures, and clinicians should have a high-index of suspicion in dancers suffering an acute injury to the foot and ankle with greater than expected pain or swelling. Multiple imaging modalities can be used to make the diagnosis, to include plain film radiographs, MRI, and CT scan. Fracture characteristics and patient-specific factors should be taken into account when deciding on a treatment plan.